Outcomes of prolonged preterm premature rupture of the membrane: a report of six cases - Dixit, Asha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Preterm premature rupture of the membranes (PROM) is associated with significant maternal morbidity and perinatal mortality. With an increasing era of infertility, the main interest of an assisted reproductive technology specialist is to increase the take-home baby rate. Here authors present report on the outcomes of prolonged preterm PROM cases facilitated with expectant management. Report is based on the medical records of six women with preterm PROM between 16-31 weeks of gestation who gave their consent to continue the pregnancy. These women were diagnosed with PROM by the litmus test and per speculum examination. Ultrasound scan and clinical investigation, which included complete blood count and C-reactive protein level, were performed in all cases. Prophylactic antibiotics were administered to prevent the infection and increase the latency period. All six babies (100%) were delivered successfully. There was no foetal mortality and maternal morbidity observed. Expectant management in preterm PROM cases can increase the survival rate and hence the take-home baby rate.